Description Of The Characteristics Of The Plasenta Retention In Children Mother - Andi Tenri Fajriani; Sri Eka Juniarli (Jurnal Life Birth, 2017)
Placental retention is a condition in which the placenta is not born until or beyond 30 minutes after the baby is born. Placental retention can cause infection and bleeding, bleeding is the number one cause of death (40% -60%) of the maternal mortality rate in Indonesia. The purpose of this study is to know the characteristics of placental retention in maternal at H.A.Sulthan Dg Radja District Hospital in Bulukumba Regency from January 2013 to December 2014. The research method uses a retrospective descriptive design, which is collecting data by looking backward. The sample in this study was to use a total sampling method that is 152 mothers. Data collection techniques in this study using the observation data matrix (checklist sheet). The results of the study according to parity in placental retention rates were more common in multiparas (42.8%), and placental retention rates according to labor interval occurred most at birth intervals close to <2 years (51.3% while the incidence rate of placental retention mostly occurred in mothers who had no history of curettage (68.4%).